Implementasi Penggunaan Dana Desa Dalam Pelestarian Adat - Eko Nuriyatman; Windarto Windarto; Rustian Mushawirya (Jurnal Selat, 2020)
This research focuses on the implementation of Village Funds in Jambi Luar Kota Subdistrict, Muaro Jambi Regency in the preservation of customary villages, where villages are autonomous regions with the passing of Law Number 6 of 2014 concerning Villages. The Village Law also provides a breath of fresh air regarding the escape of customary villages, where the previous regulations have not yet brought back the customary village clearly and firmly, but with the emergence of the Village Law it is sufficient to accommodate the Village to continue to maintain and maintain the values ​​of local wisdom. This study uses a descriptive approach, with interview data collection techniques. The Village Adat Institution must be able to cover all aspects, both in terms of customary Village management, supervision of traditional villages, customary Village government to customary Village Regulations, with the presence of Customary Institutions and having a significant role in maintaining and maintaining local cultural values ​​amidst diversity. in society, being able to implement its role without injuring the law, religious values, diversity and so on, but accelerating the realization of an Independent Village without having to erode the original culture of Jambi Luar Kota Subdistrict. The results of this research show that the implementation has been proven proven by ratifying it. The customary institutions in Jambi Luar Kota Subdistrict, it's just not optimal, because the Customary Institution is still focused on internal organizations, customary village regulations and the procurement of Sombolis infentary which is considered one of the local cultural treasures.